Developing and nurturing interpersonal communication skills through the self-directed music ensemble - Clark, Russell Edwin II (Kansas State University, 2024)
The purpose of this study was to explore how teachers utilize student self-directed music ensembles (SDMEs) in an attempt to develop certain musical and communicative skills within their students. Orchestra directors (n=3) within Kansas public schools shared their processes when implementing SMDEs into their curricula through a series of interviews with the researcher. Data analysis of interviews revealed how developing specific communication skills for chamber ensembles has perceived benefits for student music making as well as their day-to-day interactions with their peers. Emerging themes included: empathy skills, unique setting/unique opportunities, balancing teacher involvement, and develops community and connection.
Keywords: Music; Communication; Self-directed; Chamber music; Teaching